Maqashid of Harmony Indonesian Style: From Tolerance to Love - Muhammad Syukri Albani Nasution; Nurhayati Nurhayati; Ahmad Tamami Jakfar; Imam El Islamy (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to formulate the concept of Maqasid of Harmony through a critical analysis of the Ministry of Religious Affairs' document Trilogy of Harmony, Volume II. The research begins with the critique that harmony in Indonesia is often reduced to mere tolerance or social etiquette, which, in a pluralistic society, may still conceal subtle forms of domination. By integrating philosophical inquiry with the framework of Maqasid al-Shari‘ah, this study explores how the paradigm of harmony can be shifted from passive tolerance toward relationships grounded in love and recognition. The findings reveal that a maqasid-oriented notion of harmony comprises three essential dimensions: human-human relations (hifẓ al-ummah), human-environment relations (hifẓ al-bi'ah), and spiritual relations with God. The novelty of this research lies in demonstrating that safeguarding diversity and the environment is an integral part of preserving religion (hifẓ al-din) and human life (hifẓ al-nafs), thereby positioning harmony as a normative bridge between revealed values and contemporary social realities.